Proceso de atención de enfermería en paciente adulto con hernia inguinal derecha. - Mendoza Pinargote, María José (2022)
This research work deals with an older adult patient with a diagnosis of right inguinal hernia, the objective of which was to elaborate the nursing care process in an older adult patient with a diagnosis of right inguinal hernia. This topic is of vital importance because it represents a large part of the interventions currently addressed. The nursing staff should implement biosecurity, aseptic and antiseptic measures and wash their hands beforehand when performing the activities taught based on the nursing diagnosis and the nursing process to care directly for the patients, thus reducing the percentage of pathogenic microorganisms when the wound is cleaned aseptically. As a conclusion it was obtained that medical treatment as well as nursing interventions are fundamental to achieve a prompt improvement in the patient with right inguinal hernia.